Desirable ameliorations of the law - Meredith, James C. (Statistical and Social Inquiry Society of Ireland, 1940)
Those that call for respect for the law simply because it is the law and not because it expresses the conscience and will of the people and is adequate for modern requirements will call in vain?at all events, in Ireland. Nothing so undermines respect for the law as indifference to its defects: nothing fosters respect for the law so much as enthusiasm and concern for its perfection. It is this conviction that has prompted me to enquire in what directions our law has become more or less out-of-date and stands most in need of improvement. What I have to say might, however, produce an unintended impression if my observations were confined to needed reforms and was to say nothing of the improvements effected in our law in recent years, of which the legislature and all law-respecting citizens have a right to be proud. I hope, therefore, to be pardoned, for devoting a few short remarks to that matter, so that meritorious achievements and shortcomings being viewed side by side, the latter may not appear in undue proportions.
Read on Thursday, 18th April, 1940
Keywords: Legal system; Irish law; 314.15